2015
DOI: 10.1179/2046905515y.0000000044
|View full text |Cite
|
Sign up to set email alerts
|

Needs assessment to improve neonatal intensive care in Mexico

Abstract: These findings may guide efforts to improving quality of care delivery in Mexican neonatal intensive care units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…La literatura internacional insiste en la necesidad y posibilidad de iniciativas que combatan la elevada mortalidad neonatal. [17][18][19]32 Los datos de este estudio corroboran esto y evidencian la existencia de brechas importantes en la calidad de la atención en las patologías más frecuentemente implicadas en la muerte de neonatos. Esta evidencia es útil si se cuenta con datos sobre aspectos relevantes del proceso de atención, que focalicen las iniciativas de mejora, y se monitorizan los efectos de las mismas.…”
Section: Discussionunclassified
“…La literatura internacional insiste en la necesidad y posibilidad de iniciativas que combatan la elevada mortalidad neonatal. [17][18][19]32 Los datos de este estudio corroboran esto y evidencian la existencia de brechas importantes en la calidad de la atención en las patologías más frecuentemente implicadas en la muerte de neonatos. Esta evidencia es útil si se cuenta con datos sobre aspectos relevantes del proceso de atención, que focalicen las iniciativas de mejora, y se monitorizan los efectos de las mismas.…”
Section: Discussionunclassified
“…In the present study, financial constraints and lack of health insurance are identified as major factors in not being able to access quality health care facilities In India, where nearly two-thirds of healthcare provision is by the private sector, majority of the recipients pay out of pocket 5,6 . In a study from Mexico, Weiss et al reported that the principal barriers in neonatal care were family inability to pay and insufficient financial reimbursement 3 .…”
Section: Discussionmentioning
confidence: 99%
“…All physicians working in the NICU of paediatric hospitals of Hyderabad represented the study population. The data collection tool was a self-reported questionnaire The team of investigators developed the questionnaire based on existing instruments and an earlier study 2,3,4…”
Section: Methodsmentioning
confidence: 99%